PERAN STAKEHOLDER DALAM MENJAGA KEBERSIHAN OBJEK WISATA PANTAI TIKU KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Lespika Endang Sari; Siti Sofro Siddiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in South Nagari Tiku, Tanjung Mutiara Sub-District, Agam Regency, West Sumatera Province in order to obtain informations about the stakeholder's role in maintaining the cleanliness of Tiku Beach as tourism attraction. Some of issues in this research are (1) What is the role of stakeholders in maintaining the cleanliness in Tiku Beach as tourism attraction? (2) What are the obstacles that the stakeholders face in order to maintain the cleanliness in Tiku Beach as tourism attraction? The title of this research is